Can directed policy increase plant-based consumption in place of meat, to reduce GHG releases? : the case of minced products in Sweden - Gollisch, Leonie (SLU/Dept. of Economics, 2021)
A dietary transition from meat to predominantly plant-based diets is a desirable target with regards to climate change mitigation efforts. Therefore, this study aims at analysing the question if taxes and subsidies across differentiated minced products could increase people’s plant-based consumption in place of meat, to reduce greenhouse gas (GHG) emissions. A Swedish supermarket provided the instore dataset on minced products of plant-based and meat origins. We tested two policy scenarios, a taxation of external effects and the same taxation with a 10% subsidy on plant-based goods. To do so, we employed a Quadratic Almost Ideal Demand System. Results indicate that GHG in both scenarios could be reduced by decreased beef purchases. However, less meat in favour of plant-based consumption for emission mitigation cannot be reached. The obtained findings indicate that consumers highly prioritize beef and rather reduce their demand for substitutes to sustain meat purchases in case of taxation or use additional budget margins on further beef purchases once a subsidy is placed. We concluded that consumers need to perceive plant-based products as valid foods first before price-based measures could be effective and induce a dietary shift. Therefore, knowledge-based instruments to reach a shift in preferences could be used as the first measures.